LRP1 modulates the microglial immune response via regulation of JNK and NF-κB signaling pathways. Issue 1 (December 2016) - Yang, Longyu; Liu, Chia-Chen; Zheng, Honghua; Kanekiyo, Takahisa; Atagi, Yuka; Jia, Lin; Wang, Daxin; N'songo, Aurelie; Can, Dan; Xu, Huaxi; Chen, Xiao-Fen; Bu, Guojun
Abstract Background Neuroinflammation is characterized by microglial activation and the increased levels of cytokines and chemokines in the central nervous system (CNS). Recent evidence has implicated both beneficial and toxic roles of microglia when over-activated upon nerve injury or in neurodegenerative diseases, including Alzheimer's disease (AD). The low-density lipoprotein receptor-related protein 1 (LRP1) is a major receptor for apolipoprotein E (apoE) and amyloid-β (Aβ), which play critical roles in AD pathogenesis. LRP1 regulates inflammatory responses in peripheral tissues by modulating the release of inflammatory cytokines and phagocytosis. However, the roles of LRP1 in brain innate immunity and neuroinflammation remain unclear. Methods In this study, we determined whether LRP1 modulates microglial activation by knocking downLrp1 in mouse primary microglia. LRP1-related functions in microglia were also assessed in the presence of LRP1 antagonist, the receptor-associated protein (RAP). The effects on the production of inflammatory cytokines were measured by quantitative real-time PCR (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA). Potential involvement of specific signaling pathways in LRP1-regulated functions including mitogen-activated protein kinases (MAPKs) and nuclear factor-κB (NF-κB) were assessed using specific inhibitors. Results We found that knocking down ofLrp1 in mouse primary microglia led to the activation of both c-Jun N-terminal kinase (JNK) and NF-κB pathways with corresponding enhanced sensitivity to lipopolysaccharide (LPS) in the production of pro-inflammatory cytokines. Similar effects were observed when microglia were treated with LRP1 antagonist RAP. In addition, treatment with pro-inflammatory stimuli suppressedLrp1 expression in microglia. Interestingly, NF-κB inhibitor not only suppressed the production of cytokines induced by the knockdown ofLrp1 but also restored the down-regulated expression ofLrp1 by LPS. Conclusions Our study uncovers that LRP1 suppresses microglial activation by modulating JNK and NF-κB signaling pathways. Given that dysregulation of LRP1 has been associated with AD pathogenesis, our work reveals a critical regulatory mechanism of microglial activation by LRP1 that could be associated with other AD-related pathways thus further nominating LRP1 as a potential disease-modifying target for the treatment of AD.